Drug-induced esophageal ulcers: Case series and the review of the literature - Sait Dağ, Muhammed; Abidin Öztürk, Zeynel; Akın, İrem; Tutar, Ediz; Çıkman, Öztekin; Gülşen, Murat Taner (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Drugs can cause several complications in the esophagus and lead to pill esophagitis. In this paper, our purpose is to share our clinical experience in light of the literature and put forward the general characteristics of pill esophagitis. Materials and Methods: In our clinic, between January 2008 and June 2012, by excluding other factors, 48 patients were included in the study, diagnosed as drug-induced esophagitis with their history, endoscopic view, and histopathologic evaluation. Results: There were 34 (70.9%) female and 14 (29.1%) male patients in the study, and their average ages were 35.1 and 32.4, respectively. Clinical symptoms were odynophagia (79.1%), retrosternal pain (62.5%), and dysphagia (47.9%). The reason for these symptoms for 85.5% of the patients was related to insufficient water consumption while taking the pill, taking the pill in recumbent position, or both. Tetracycline and its variant, doxycycline, were responsible for 52% of the patients, and 62.5% of the drugs were in capsule form. Ulcers were at the proximal and middle third of the esophagus in 79.2% of the patients. In the histopathologic evaluation, nonspecific acute inflammatory changes were found in 29.1% of the cases. Various proton pump inhibitors and sucralfate were used in the treatment. While no perforation and structure were detected, 1 patient died because of repetitive arterial bleeding. Conclusion: Almost every kind of drug, particularly doxycycline, can cause ulcer in the esophagus. Pill esophagitis can be prevented by warning patients about drinking water sufficiently and sitting up while taking the pill.